Influence of Cryopreserved Human Placental Tissue on Reparative Bone Formation in Rats with the Lower Jaw Open Fracture on Osteoporosis Background - Likhitskyi, Oleksii O.; Goltsev, Anatoliy M. (Problems of Cryobiology and Cryomedicine, 2019)
The influence of calcium citrate and cryopreserved human placental tissue reparative osteogenesis in ratsÂ with an open fracture of the lower jaw on the background of osteoporosis was investigated. The studies were performed in three groups (n = 35 each) of mature Wistar male rats (180â€“200 g weight): the rats with a simulated open mandibularÂ fracture on the osteoporosis background, rats with simulated pathology, which implanted with the cryopreserved humanÂ placental tissue and the rats with a simulated pathology, which in addition to an implantation of the cryopreserved human placental tissue were also injected with calcium citrate. Experimental osteoporosis in rats was induced by injecting ofÂ 60% solution of hydrocortisone acetate for 60 days in a dose of 50 mg/kg every 24 hours. Afterwards traumatic damage toÂ the lower jaw was simulated. The model showed that cryopreserved placental tissue had an osteoprotective effect, whichÂ was manifested in enhancing the collagen formation processes (maximum to day 30), as well as bone mineralization,Â depriving the effect on osteo-destructive processes and collagen catabolism (maximum to day 14). The combined useÂ of cryopreserved human placenta and calcium citrate had a powerful osteoprotective effect, which also developed at theÂ early stages of experiment if compared wuith monotherapy. Probl Cryobiol Cryomed 2019; 29(2):125â€“136.